1988
DOI: 10.1177/003368828801900103
|View full text |Cite
|
Sign up to set email alerts
|

First Language Composition Pedagogy in the Second Language Classroom: A Reassessment

Abstract: Much of current L2 writing theory has been extrapolated from L 1 literature on native speaker writing processes (Zamel 1982(Zamel , 1983Raimes 1985). This has led to an influx of Ll instructional practices into L2 classrooms which remain largely untested on non-native populations. As a relatively new applied field, the teaching of composition to non-natives has been largely dependent upon the pedagogical practices modelled on research findings and practical experiences of first language composition teachers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, in Sasaki (2002), although the participating students significantly improved their composition scores, they did not improve fluency (in terms of either quantity or speed) after 2 semesters of processwriting instruction. Furthermore, some other previous studies reported a lack of improvement in L2 writers' composition quality and/or fluency as a result of instruction (e.g., Ross et al, 1988;Shi, 1998). As for the effects of the participants' studyabroad experiences, previous studies have reported that gains in L2 proficiency and fluency in other skills (reading, listening, and speaking) were possible as the result of such experiences (e.g., Brecht, Davidson, & Ginsberg, 1995;Freed, 1995b), but no study seems to have examined gains in terms of L2 writing (Freed, 1995a).…”
Section: Composition Scores and Writing Fluencymentioning
confidence: 97%
See 1 more Smart Citation
“…However, in Sasaki (2002), although the participating students significantly improved their composition scores, they did not improve fluency (in terms of either quantity or speed) after 2 semesters of processwriting instruction. Furthermore, some other previous studies reported a lack of improvement in L2 writers' composition quality and/or fluency as a result of instruction (e.g., Ross et al, 1988;Shi, 1998). As for the effects of the participants' studyabroad experiences, previous studies have reported that gains in L2 proficiency and fluency in other skills (reading, listening, and speaking) were possible as the result of such experiences (e.g., Brecht, Davidson, & Ginsberg, 1995;Freed, 1995b), but no study seems to have examined gains in terms of L2 writing (Freed, 1995a).…”
Section: Composition Scores and Writing Fluencymentioning
confidence: 97%
“…One of the most important, but lacking, aspects of the model was the one that is related to ''general stages of writing development'' (Grabe, 2001, p. 48). Very few previous studies to date (e.g., Lee, 2002;Ross, Shortreed, & Robb, 1988) have observed L2 writers for longer than 1 semester (cf. Berg, 1999;Shi, 1998).…”
mentioning
confidence: 99%
“…Picture sequences were selected for their clear story line and because writing stories about them did not necessarily require prior knowledge of the subject, which might have affected the students' writing. In addition, a number of researchers (Ishikawa, 1995;Ross, Shortreed, & Robb, 1988;Rousseau, Bottge, & Dy, 1993) have used similar picture sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Although a number of articles and books have discussed the advantages of using journals (Davies, 2001;Fulwiler, 1987;Gutstein, Batterman, Harmatz-Levin, Kreeft, & Meloni, 1983;Holmes & Moulton, 1997;Kelen, 2001;Kreeft, 1984;Kresovich, 1988;Leki, 1985;Peyton, l990a;Peyton, l990b;Peyton & Reed, l990;Staton, 1987;Werderich, 2002), only a few researchers have investigated the question of improvement in journal writing over time (Barba, 1992;Casanave, 1993Casanave, , 1994Duppenthaler, 2002a;Kreeft, 1984), and even fewer have investigated the possibility of a transfer-of-skills effect from journal writing to other types of writing (see for example Abdel Fattah, 1993;Hirose & Sasaki, 2000;and Ross, Shortreed, & Robb, 1988). Do the gains, for example in fluency or accuracy, reported in journals carry over into other types of writing?…”
Section: Introductionmentioning
confidence: 99%
“…The picture sequence was selected for its clear story line and because it did not require prior knowledge of the subject. A number of researchers (Ross, Shortreed, & Robb, 1988;Rousseau, Bottge, & Dy, 1993;Ishikawa, 1995) have used similar picture sequences to gather writing samples from students.…”
Section: Methodsmentioning
confidence: 99%